Cell autonomous requirement of neurofibromin (Nf1) for postnatal muscle hypertrophic growth and metabolic homeostasis. Issue 6 (19th October 2020) - Wei, Xiaoyan; Franke, Julia; Ost, Mario; Wardelmann, Kristina; Börno, Stefan; Timmermann, Bernd; Meierhofer, David; Kleinridders, Andre; Klaus, Susanne; Stricker, Sigmar
Abstract: Background: Neurofibromatosis type 1 (NF1) is a multi‐organ disease caused by mutations in neurofibromin 1 ( NF1 ). Amongst other features, NF1 patients frequently show reduced muscle mass and strength, impairing patients' mobility and increasing the risk of fall. The role of Nf1 in muscle and the cause for the NF1‐associated myopathy are mostly unknown. Methods: To dissect the function of Nf1 in muscle, we created muscle‐specific knockout mouse models for NF1, inactivating Nf1 in the prenatal myogenic lineage either under the Lbx1 promoter or under the Myf5 promoter. Mice were analysed during prenatal and postnatal myogenesis and muscle growth. Results: Nf1 Lbx1 and Nf1 Myf5 animals showed only mild defects in prenatal myogenesis. Nf1 Lbx1 animals were perinatally lethal, while Nf1 Myf5 animals survived only up to approximately 25 weeks. A comprehensive phenotypic characterization of Nf1 Myf5 animals showed decreased postnatal growth, reduced muscle size, and fast fibre atrophy. Proteome and transcriptome analyses of muscle tissue indicated decreased protein synthesis and increased proteasomal degradation, and decreased glycolytic and increased oxidative activity in muscle tissue. High‐resolution respirometry confirmed enhanced oxidative metabolism in Nf1 Myf5 muscles, which was concomitant to a fibre type shift from type 2B to type 2A and type 1. Moreover, Nf1 Myf5 muscles showed hallmarks of decreased activation of mTORC1 and increased expression of atrogenes. Remarkably, loss of Nf1 promoted a robust activation of AMPK with a gene expression profile indicative of increased fatty acid catabolism. Additionally, we observed a strong induction of genes encoding catabolic cytokines in muscle Nf1 Myf5 animals, in line with a drastic reduction of white, but not brown adipose tissue. Conclusions: Our results demonstrate a cell autonomous role for Nf1 in myogenic cells during postnatal muscle growth required for metabolic and proteostatic homeostasis. Furthermore, Nf1 deficiency in muscle drives cross‐tissue communication and mobilization of lipid reserves.